Indeks Komposit Pekerjaan Layak di Indonesia Pada Era Pandemi COVID-19 - Katamso Noto Santoso; Suryo Adi Rakhmawan (Politeknik Statistika STIS, 2021)
The pandemic has an impact on various levels of socio-economic life, including employment. The impact of reducing working hours, temporarily not working, unemployment, or being out of the labour force is felt by formal and informal workers. Moreover, informal workers have become a vulnerable workforce. These problems make it necessary to know how the conditions of employment in Indonesia are during the pandemic. This study calculates the Decent Work Index (DWI) during the pandemic in Indonesia, which aims to find out the description of the provinces in Indonesia so that relevant parties can carry out planning to careful evaluation. This study found that several areas still have low DWI using factor analysis. This means that the central and local governments in the related areas should be more sensitive and responsive to the work worthiness of the population, starting from focusing on variables that have a significant impact.